Impaired cortisol awakening response in eating disorder women with childhood trauma exposure: evidence for a dose-dependent effect of the traumatic load. Issue 6 (29th August 2017) - Monteleone, A. M.; Monteleone, P.; Volpe, U.; De Riso, F.; Fico, G.; Giugliano, R.; Nigro, M.; Maj, M.
Abstract : Background: Childhood trauma is a non specific risk factor for adult eating disorders (ED), and the hypothalamic-pituitary-adrenal (HPA) axis seems to mediate such a risk. Here we explored the impact of different types of childhood trauma and of traumatic load on the cortisol awakening response (CAR) of women with anorexia nervosa (AN) or bulimia nervosa (BN). Methods: Saliva samples were collected at awakening and after 15, 30, 60 min to measure cortisol levels by 121 women (44 AN patients, 36 BN patients and 41 healthy women). Participants filled in the Childhood Trauma Questionnaire. Results: AN and BN patients with childhood maltreatment exhibited an attenuated CAR compared with non-maltreated ones. In the whole ED patient group, the CAR showed a progressive impairment with the increasing number of reported trauma types. Although significant negative correlations emerged between the type or the number of traumas and the CAR, only the number of traumas remained significantly associated with the CAR in a stepwise multiple regression analysis. Conclusions: Present findings confirm that childhood trauma is associated with an impaired CAR in adult AN and BN patients and demonstrate for the first time a negative dose-dependent effect of the traumatic load on HPA axis activity.